Optimal Coordinated Frequency Regulation of Renewable Energy Systems via an Equilibrium Optimizer - Zhao, Mintong; Huan, Jiajia; Huang, Xin; Yu, Tao; Ding, Qiaoyi (Frontiers in Energy Research, 2022)
With the urgency of environmental protection, wind power and photovoltaic (PV) projects continue to be implemented, and the proportion of renewable energy in the power grid will be higher and higher. Therefore, wind power and PV also began to participate in the regional power grid frequency regulation (FR), and gradually replace the role of thermal power units in the power grid. To study the characteristics of renewable energy in frequency modulation, an automatic generation control (AGC) model of wind power and photovoltaic participating in the power grid FR is established. At the same time, an equilibrium optimization (EO) is proposed to allocate the total power in real-time, so as to improve the FR performance by quickly obtaining the optimal power distribution scheme. The simulation results on the proposed model show that the proposed method is feasible.